Study Motivation, Academic Performance and Career Commitment in Accounting Profession - handoyo, sofik (Fakultas Ekonomi, Universitas Negeri Semarang, 2018)
The aim of the research is to examine the relationship between students' motivation, academic performance and career commitment to accounting profession among undergraduate accounting students. The sample of the study involved 101 undergraduate accounting students of Universitas Padjadjaran. Purposive sampling technique was used in this study. There are three independent variables investigated in this study, namely study motivation, academic performance and commitment carrier in the accounting profession. Intrinsic interest, extrinsic interest, normative belief and conflict anticipation was treated as sub-variable of the study motivation. Descriptive analysis along with bivariate correlation analysis was applied in this study. The results indicated that majority of accounting undergraduate student choosing accounting study program due to intrinsic interest motivation and extrinsic interest motivation and there is no indication motivation influenced by normative believe motivation and conflict anticipation motivation. Intrinsic interest has a positive and significant correlation with academic performance (r=2.17, p<0.01) and academic performance has a positive correlation (r = 0.124) with commitment carrier in the accounting profession.